Coastal processes and geomorphologic characteristics of major coastal towns in East Sabah for assessment of Tsunami impacts - Felix Tongkul; Ejria Saleh (Universiti Malaysia Sabah, 2009)
The major coastal town of East Sabah, comprising of Sandakan, Lahad Datu, Semporna and Tawau are characterized by extensive mangrove swamps, narrow sandy beaches and rocky coastlines. Most of the town areas are built on reclaimed mangrove swamps. The Sandakan and Tawau town areas are exposed to the open Sulu and Celebes seas, respectively, whereas the towns of Lahad Datu and Semporna are sheltered from the open sea by the Sakar and Bum-bum islands, respectively. Numerical tsunami modeling, using worse-case scenarios indicate that all towns are exposed to tsunami waves up to 2 meters within 1 hour time. On a regional scale, Tawau area is found to be exposed to highest risk of tsunami due to its narrow shelf, followed by Sandakan and Lahad Datu areas. On a local scale, areas found to be of highest risks are settlements located along the coast, especially water villages located in all the town areas. Based on tsunami risk maps prepared for each town, a general plan for tsunami hazard mitigation is proposed, which includes tsunami hazard emergency evacuation route maps for each town area.